Frequency of AmpC β-lactamase Resistance in Escherichia coli Isolates from Urinary Tract Infections in Gorgan, Iran - Mahdi Arab Zoozani; Ezzat Allah Ghaemi; Ailar Jamalli (Golestan University Of Medical Sciences, 2017)
Introduction: AmpC β-lactamases are among the most important cephalosporinases. Production of AmpC β-lactamase in microorganisms is often associated with multidrug resistance and limited treatment options. This study aimed to determine antimicrobial susceptibility pattern and frequency of AmpC β-lactamase genes in Escherichia coli strains isolated from urinary tract infections. Materials and Methods: The study included 154 E. coli isolates from urine samples of patients in medical centers of Gorgan, Iran. Cefoxitin-resistance was evaluated by the Kirby-Bauer method.  Cefoxitin-resistant strains were evaluated using cefoxitin disks alone and combined with boronic acid to confirm presence of AmpC β-lactamase. Presence of MOX gene was investigated by polymerase chain reaction. Results: Among the 154 E. coli isolates, 37 (24%) were cefoxitin-resistant, 16 of which were found to be AmpC β-lactamase-positive in the phenotypic test. In addition, the MOX gene was found in two isolates. Conclusions: The frequency of AmpC β-lactamase-producing E. coli and MOX gene in Gorgan is close to the regional and national average.